2018
DOI: 10.7567/jjap.57.096102
|View full text |Cite
|
Sign up to set email alerts
|

Effective species for ignition of premixed burner flame in effluent of dielectric barrier discharge

Abstract: The ignition probability of a premixed burner flame was improved in the effluent of a dielectric barrier discharge. In addition, the propagation speed of the flame kernel was increased by the dielectric barrier discharge. The increase in the propagation speed of the flame kernel was more significant in the region close to the nozzle of the effluent gas. We measured the spatial distributions of the densities of OH and atomic oxygen in the effluent. We found that the axial decay of the density of atomic oxygen w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Targeted species are produced by discharges generated in fuel-air mixtures, with a potential impact on combustion chemistry. For example, atomic oxygen (O) [23][24][25] and atomic hydrogen (H) [26], have been measured in different plasma-assisted combustion configurations. Similarly, several studies have reported on the measurements of methylidyne radicals (CH) [27] and hydroxyl radicals (OH) [5,24,[28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeted species are produced by discharges generated in fuel-air mixtures, with a potential impact on combustion chemistry. For example, atomic oxygen (O) [23][24][25] and atomic hydrogen (H) [26], have been measured in different plasma-assisted combustion configurations. Similarly, several studies have reported on the measurements of methylidyne radicals (CH) [27] and hydroxyl radicals (OH) [5,24,[28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…For example, atomic oxygen (O) [23][24][25] and atomic hydrogen (H) [26], have been measured in different plasma-assisted combustion configurations. Similarly, several studies have reported on the measurements of methylidyne radicals (CH) [27] and hydroxyl radicals (OH) [5,24,[28][29][30]. However, these studies focused mainly on ignition or on enhancement of combustion by non-equilibrium discharges at sub-atmospheric pressures.…”
Section: Introductionmentioning
confidence: 99%